2021
DOI: 10.1021/acsnano.1c05857
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Fabrication and Use of 3D Structured Microparticles Spatially Functionalized with Biomolecules

Abstract: Microparticles with defined shapes and spatial chemical modification can enable new opportunities to interface with cells and tissues at the cellular scale. However, conventional methods to fabricate shaped microparticles have trade-offs between the throughput of manufacture and precision of particle shape and chemical functionalization. Here, we achieved scalable production of hydrogel microparticles at rates of greater than 40 million/hour with localized surface chemistry using a parallelized step emulsifica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(73 citation statements)
references
References 34 publications
0
73
0
Order By: Relevance
“…Our nanovial technology can be easily scaled up to process millions of cells per day. Here, we fabricated nanovials using a flow-focusing device at rate of 5.6 million/hour, and higher production rates can be achieved using parallelized microfluidic device 17 . For each secretion assay, we loaded 0.23 million cells into 187,000 nanovials in a 24-well plate yielding ~28,000 cells loaded in nanovials.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our nanovial technology can be easily scaled up to process millions of cells per day. Here, we fabricated nanovials using a flow-focusing device at rate of 5.6 million/hour, and higher production rates can be achieved using parallelized microfluidic device 17 . For each secretion assay, we loaded 0.23 million cells into 187,000 nanovials in a 24-well plate yielding ~28,000 cells loaded in nanovials.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…with in vitro or animal models) or transcriptomic information (either pooled or using single-cell sequencing technologies). In our previous studies, we have shown that the morphology of the nanovial cavity protects cells during damaging sorting steps, leading to improved viability, cell expansion and proliferation post-sort 16,17 . The ability to functionally sort viable intact cells will allow improved understanding of unique polyfunctional phenotypes.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 3 more Smart Citations